In pursuit of a narrative pedagogy: a study with primary school teachers - Davis, Charlie (2018)
Within cultures, some narratives of everyday life are elevated to positions of canonicity, whereby they are tacitly accepted as common-sense accounts of everyday shared realities. Such narratives can often perpetuate norms, rituals and values which sustain perceptions of sameness and otherness at intra and inter-group levels. My interest in this theme developed out of my personal experiences growing up in a Protestant community in rural Northern Ireland during the Troubles; a period of sectarian conflict officially lasting from 1969 to 1998. Through cultural forms such as traditions, school curricula, folklore and family, narratives circulated which sustained powerful sectarian representations of ‘Us’ and ‘Them’. Such dominant narrative forms had the power to silence other narratives which challenged their authenticity as universal folk theories explaining why the social worlds people lived in were organised as they seemed to be. Although this work has its roots in my life history, it was not possible for me to pursue a doctoral study exploring these issues in Northern Ireland. Therefore, I worked with a group of primary school teachers because I considered their lives to be rich in dominant, secret and resistance narratives. This study sits across a range of disciplinary areas where concepts of narrative inform the means, the object and the product of the inquiry. Theories articulating the narrative construction of everyday realities and the value of narrative pedagogies were key in framing the pedagogic and methodological focus of the study. I drew on the work of Jerome Bruner to develop a theoretical framework within which to articulate the aims and focus of this study. I looked to scholars such as Ivor Goodson to develop a conceptual understanding of how a narrative pedagogy might be mobilised as part of inquiries exploring people’s everyday lived experiences. Working with these sources and empirical studies discussing the creation of counter storytelling spaces, I pursued the key pedagogic principle of narrative disruption. I did so to prompt the teachers to consider constructing alternative narratives about their lived experiences in response to narrative forms presented to them as dominant representations of teachers’ lives. The study took place in a primary school, which I have given the pseudonym Midview Primary School, in the Midlands of England. Over a five-week period, the teachers participated in weekly sessions, scaffolding their capabilities to use different digital resources to create alternative narrative representations of key incidents from their lives. I generated data through participant observations, post-session feedback questionnaires, participants’ final narratives, mind maps and semi-structured interviews. Through a reflective analysis of the data, one which accounted for my position in the inquiry, I found that while the participants valued having a space in which to talk about their lives as teachers, they were reluctant to challenge narratives presented to them as dominant representations of their lives. The inquiry space became an echo chamber where dominant narrative themes of oppression, self-sacrifice, stoicism, and altruism were reproduced to guard against perceived external interference from performative bodies. I discuss how social dynamics within the group, residual traces of the work day and my positionality as someone known to the group made the creation of alternative narratives difficult. The thesis ends with a critical reflection aimed at articulating how outcomes from this study will inform future similar studies. By way of proposing a revised pedagogic rationale, I have imagined how this might look in a Northern Irish context, seeking to challenge canonical narratives sustaining sectarian division. This ‘imagining’ takes the form of two narratives: one depicting an account of the study using the original approach I took with the teachers and the other representing experiences based on a revised approach informed by the outcomes of this study.